PENGARUH INTEGRETED MARKETING COMMUNICATION TERHADAP MINAT BERKUNJUNG PADA DESTINASI WISATA SAAT PANDEMI COVID-19 (STUDI KASUS WISATA KANDANG SAPI WONOSALAM JOMBANG) - Rosyida, Aulia; Fahimah, Mar'atul (Jurnal Ecoment Global, 2021)
The impact of Covid-19 on tourism is reflected in the decline in the number of domestic and foreign tourists. The decline in the transportation sector and the provision of accommodation and catering services is the beginning of poor working conditions in the tourism sector. KANSA or Wonosalam Cow Cage is an educational and fun vehicle with a modern packing farm concept. KANSA Wonosalam is located on Jalan Anjasmoro in Tukum Hamlet, Wonosalam District, Jombang Regency. The COVID-19 pandemic requires everyone to avoid crowded places, including tourist attractions. At this time the most important health conditions. After more than 1 year of the COVID-19 pandemic, people are starting to need a place for entertainments. The purposee of this study was to determine IMC (integrated marketing communication) on interest in visiting tourist destinations during the COVID-19 pandemic. This study uses quantitative statistical research techniques. The population in this study were all visitors to the KANSA tourist destination during the pandemic. The IMC variables used are advertising, sales promotion, public relations on visiting interest. The sampling technique was purposive sampling. The data analysis method used is multiple linear regression analysis. The results of this study indicate that advertisinng, salles promotionn, public relationss have an influence on interest in visiting tourist destinations during the covid-19 pandemic.